Spatiotemporal associations between incidence of type 1 diabetes and COVID-19 vaccination rates in children in Germany: a population-based ecological study - Kamrath, Clemens; Eckert, Alexander J.; Lignitz, Sarah; Hillenbrand, Nikolas; Dost, Axel; Warncke, Katharina; Klose, Daniela; Grohmann-Held, Karina; Holl, Reinhard W.; Rosenbauer, Joachim (The journal of pediatric endocrinology and metabolism, 2025)
Objectives The incidence of type 1 diabetes (T1D) in children increased during the first two years of the COVID-19 pandemic and declined thereafter. It is not known whether the decline is associated with COVID-19 vaccination rates in children. This study investigates whether COVID-19 vaccination rates are associated with T1D incidence in children. Methods Population-based ecological study of children with new-onset T1D in the years 2022 and 2023 from the German Prospective Diabetes Registry. COVID-19 vaccination rates (VR) for 2022 were obtained from the Digital Vaccination Rate Monitoring-Project of the Robert-Koch-Institute. Spatial Spearman correlation analysis between period-averaged COVID-19 VR and T1D standardized incidence ratios (SIR) per county were used for the year 2022. Bayesian conditional autoregressive (CAR) Poisson models, including a time lag of 0-12 months between COVID-19 VR and T1D SIR, were used to assess their association. Results Data of 6,736 children and adolescents with new-onset T1D in the years 2022 and 2023 and of 4,208,377 vaccinated children aged 5-17 years across 336 German counties were analyzed. Neither the month-averaged spatial analysis (5-11 years: r=−0.029 [95%CI −0.136; 0.079]; 12-17 years: r=0.031 [95%CI −0.077; 0.138]) nor the spatiotemporal CAR models including time shifts of 0-12 months showed significant correlations between T1D SIR and COVID-19 VR. Conclusions This study found no significant associations between childhood COVID-19 vaccination rates and the subsequent incidence of type 1 diabetes over the next 12 months. Further research is needed to investigate the relationship in younger children.
Gesehen am 02.02.2026